2016
DOI: 10.3390/dj4040045
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the Jaws (ONJ) after Bisphosphonate Treatment in Patients with Multiple Myeloma: Decreasing ONJ Incidence after Adoption of Preventive Measures

Abstract: Bisphosphonates (BPs) are administered to Multiple Myeloma (MM) patients with bone lytic lesion. Osteonecrosis of the Jaw (ONJ) is a complication reported since 2003 in patients treated with intravenous (IV) BPs such as zoledronic acid and pamidronate, with 6%–26.3% frequency in early literature series, before some preventive measures were recommended. We evaluated the occurrence of ONJ with and without dental preventive measures in MM patients treated with BPs in our centre between 1996 and 2015. Since 2005, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 53 publications
(78 reference statements)
0
4
0
2
Order By: Relevance
“…As suggested previously, the benefits of continuation of BP therapy in a population with high fracture risk (Black et al, ) may outweigh the risk of developing ONJ. Furthermore, if dental interventions are inevitable, cautious approaches, including preventive dental screening to identify any possible infection or inflammation (Catania et al, ) and refining surgical protocols for dental surgery (Scoletta et al, ), may be considered. Finally, clinical decisions on the length of BP holidays and dental surgery should be based on a risk‐benefit analysis considering individual patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested previously, the benefits of continuation of BP therapy in a population with high fracture risk (Black et al, ) may outweigh the risk of developing ONJ. Furthermore, if dental interventions are inevitable, cautious approaches, including preventive dental screening to identify any possible infection or inflammation (Catania et al, ) and refining surgical protocols for dental surgery (Scoletta et al, ), may be considered. Finally, clinical decisions on the length of BP holidays and dental surgery should be based on a risk‐benefit analysis considering individual patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in the present study are comparable for the patients who did not have a check-up with an oral cavity specialist (i.e., 50 patients in group 0, and 5 vs. 21 belonging to groups 1–2–3–4) [ 33 ]. A meaningful reduction in the risk of MRONJ among multiple myeloma patients treated with BPs was confirmed if preventive measures had been adopted [ 17 ]. In our sample, MRONJ was observed in 3/21 patients (14.2%) who started BP treatment at a time before the risk of MRONJ had come to light; 2/20 patients (10%) who started taking BPs without any preventive dental check-up; and none of the patients whose BP therapy started only after preventive dental care measures (0%) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main target of primary prevention in patients who are to be administered drugs potentially associated with the onset of MRONJ is to achieve and maintain a state of oral and dento-periodontal health and perfect oral hygiene, thereby eliminating local risk factors [18]. It has been demonstrated that preventive dental screening and treatment reduces the incidence of MRONJ [17,19,20]. Appropriate preventive oral surgery and conservative endodontic and prosthetic measures have been published [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018 [ 7 ] 55 8 Wochen I–III Nein Operative Therapie 80–92 % (je nach Verfahren) Nicht angegeben 18/24 Giudice et al. 2020 [ 4 ] 129 15 Wochen I–II Nein Operative Therapie > 90 % Nicht angegeben 20/24 …”
Section: Ergebnisseunclassified